Application of direct stochastic optical reconstruction microscopy (dSTORM) to the histological analysis of human glomerular disease. (21st May 2021) - Garcia, Edwin; Lightley, Jonathan; Kumar, Sunil; Kalita, Ranjan; Gőrlitz, Frederik; Alexandrov, Yuriy; Cook, Terry; Dunsby, Christopher; Neil, Mark AA; Roufosse, Candice A; French, Paul MW
Abstract: Electron microscopy (EM) following immunofluorescence (IF) imaging is a vital tool for the diagnosis of human glomerular diseases, but the implementation of EM is limited to specialised institutions and it is not available in many countries. Recent progress in fluorescence microscopy now enables conventional widefield fluorescence microscopes to be adapted at modest cost to provide resolution below 50 nm in biological specimens. We show that stochastically switched single‐molecule localisation microscopy can be applied to clinical histological sections stained with standard IF techniques and that such super‐resolved IF may provide an alternative means to resolve ultrastructure to aid the diagnosis of kidney disease where EM is not available. We have implemented the direct stochastic optical reconstruction microscopy technique with human kidney biopsy frozen sections stained with clinically approved immunofluorescent probes for the basal laminae and immunoglobulin G deposits. Using cases of membranous glomerulonephritis, thin basement membrane lesion, and lupus nephritis, we compare this approach to clinical EM images and demonstrate enhanced imaging compared to conventional IF microscopy. With minor modifications in established IF protocols of clinical frozen renal biopsies, we believe the cost‐effective adaptation of conventional widefield microscopes can be widely implemented to provide super‐resolved image information to aid diagnosis of human glomerular disease.